Effect of pre-treatment on anaerobic biodegradability of Gracilaria verrucosa. Issue 1 (April 2020) - Suhartini, S; Sihaloho, R; Rahmah, N L; Nurika, I; Junaidi, M A; Paul, R; Melville, L
Abstract: In global world, increasing needs of energy is parallel to the increase of population. The limitation of land availability and change of land use has turning the focus into marine biomass, especially macroalgae, as renewable energy feedstocks. Indonesia is one of the biggest countries producing marine macroalgae. The aim of this research was to evaluate the impact of washing pre-treatment on the characteristics of macroalgae and its biodegradability in anaerobic digestion process. In this study, a biochemical methane potential (BMP) test was carried out using fresh macroalgae, specifically Gracilaria verrucosa . The ratio of inoculum to substrate was 6:1 with operation temperature of 37 °C and incubated for 28 days. Prior the BMP test, the G. verrucosa samples were washed with flowing water for 10 minutes. The findings confirmed for washing pre-treatment was significantly enhance cumulative biogas and methane production by more than 50%. The specific methane potential (SMP) of washed G. verrucosa increased by six-fold, with the value of 0.108 m 3 CH4 / kg VS. In this case, reduction of salinity concentration after washing may play an important role in increasing the anaerobic degradability. It was estimated that a high electricity potential is generated from anaerobic digestion of G. verrucosa after washing pre-treatment.